LITERATURE REVIEW ON CNS TUMORS - Salokhiddinov Khabibullo Adhamjon ugli; Khaitova Anora Tojimuradovna (European Science Publishing, 2025)
The review aims to provide a comprehensive understanding of CNS tumors, highlighting ongoing research and identifying areas where further exploration is needed.